PELATIHAN PENGGUNAAN TEKNOLOGI DIGITAL PADA APLIKASI KVISOFT FLIPBOOK MAKER DI MTS ISLAMIYYAH SEI KAMAH II - Purba, Oktaviana Nirmala; Herawati, Tuti; Susmita, Devi Facharaini; Sari, Lusi Nolita; Syahriani, Nurul (Smart Education, 2025)
Curriculum demands that continue to develop provide challenges for educators to continue updating digital capabilities that really support independent curriculum learning. The use of digital is able to change the paradigm from focusing on printed books towards using digital books with good quality content, attractive, interactive and cost-effective design and appearance. The importance of digital books can make it easier for students to use them anywhere and anytime. One application that can use digital books is Kvisoft Flipbook Maker. However, the phenomenon that occurs in the field is that the majority of students do not know and are not able to design teaching modules using the Kvisoft flipbook maker application. Because the training activities carried out by the community service team aim to improve teachers' abilities in creating and designing teaching modules using the Kvisoft flipbook maker application. The service was carried out at MTS Islamiyyah Sei Kamah II with 30 teachers involved in taking part in training activities. The training went smoothly, the students were very enthusiastic and focused in participating in the training. The average effective training achievement was 88,70%.Keyword: Teaching Module, Kvisoft Flipbook Maker, Digital Learning